Development of curriculum management in the world of education - Sabrina, Elsa; Giatman, Muhammad; Ernawati, Ernawati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The research objective is to develop curriculum management in an effort to improve the quality of education. The method used is qualitative with descriptive research. Efforts to improve the quality of education must be supported by all parties, both by managers of educational institutions at the central, regional and school levels, especially in classroom learning. In the implementation of education, each region should have a curriculum management which is an elaboration or implementation of the educational curriculum set by educational institutions. This is in accordance with the demands of the curriculum, where both the local government and even the school level are given the freedom to describe programs to improve the quality of education. The parties involved in curriculum development are the government, principals, teachers and students. The results of this curriculum management study have a concept as the main determinant of school activities in an effort to improve the quality of education.